PERSEPSI GURU FIQIH DALAM KONSEP PENDIDIKAN (STUDI PENERAPAN KURIKULUM MERDEKA DI MIN 1 MATARAM) - Baiq Ida Astini; Aqodiahi; Niswatun Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to offer a comprehensive overview of how Fiqh teachers' perceptions contribute to the implementation of this curriculum. It will also examine how these perceptions affect teaching and learning processes in the classroom and their impact on student outcomes. The research employs a descriptive qualitative method, with data collected from primary and secondary sources. Data analysis uses an interactive cycle model, involving several steps from data collection to presentation and verification. The study reveals that Fiqh teachers' perceptions of the Merdeka Curriculum are generally positive but also identify several challenges. Teachers view the Merdeka Curriculum as a beneficial innovation in education, although they acknowledge that the transition from the 2013 Curriculum is not significantly different due to their interconnectedness. Teachers find that the new curriculum allows for greater flexibility in teaching, with a shift toward a student-centered approach. However, implementation faces challenges such as inadequate facilities, lack of readiness, and increased administrative burdens. Teachers report that while their role in the classroom has shifted to being facilitators and motivators, their administrative responsibilities have increased. There are also issues with the synergy between students, parents, teachers, and the school, affecting the effectiveness of the curriculum.